Social ADS in Higher Education: Análisis de la publicidad en las redes sociales de las principales universidades españolas - Abuín Vences, Natalia; García Rosales, Daniel Francisco (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Social ads offer multiple advantages to advertisers, including a rapid increase in the visibility of brands and their services. Facebook Ads and Instagram Ads are among the most popular advertising solutions worldwide. This research analyzes the advertising actions carried out on these platforms by the Spanish universities with the largest number of students. The results corroborate the continuous evolution of online advertising. This work also reveals new developments and trends of the main brands in the education sector implemented in social ads.